2012
DOI: 10.1007/128_2012_349
|View full text |Cite
|
Sign up to set email alerts
|

Endosialidases: Versatile Tools for the Study of Polysialic Acid

Abstract: Polysialic acid is an α2,8-linked N-acetylneuraminic acid polymer found on the surface of both bacterial and eukaryotic cells. Endosialidases are bacteriophage-borne glycosyl hydrolases that specifically cleave polysialic acid. The crystal structure of an endosialidase reveals a trimeric mushroom-shaped molecule which, in addition to the active site, harbors two additional polysialic acid binding sites. Folding of the protein crucially depends on an intramolecular C-terminal chaperone domain that is proteolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 202 publications
(335 reference statements)
0
20
0
Order By: Relevance
“…Owing to the high specificity of depolymerases, it was suggested that enzyme-based capsular typing may be more useful than whole phage typing (Hsu et al 2013; Lin et al 2014). The analogous approach has been successfully applied to develop an endosialidase-based detection reagent for identification of polysialic acid-containing bacteria as well as eukaryotic cells (Jakobsson et al 2015). As a detection tool, these enzymes are used in a catalytically inactive form, capable to recognize and bind the substrate, but without its degradation.…”
Section: Polysaccharide Depolymerasesmentioning
confidence: 99%
“…Owing to the high specificity of depolymerases, it was suggested that enzyme-based capsular typing may be more useful than whole phage typing (Hsu et al 2013; Lin et al 2014). The analogous approach has been successfully applied to develop an endosialidase-based detection reagent for identification of polysialic acid-containing bacteria as well as eukaryotic cells (Jakobsson et al 2015). As a detection tool, these enzymes are used in a catalytically inactive form, capable to recognize and bind the substrate, but without its degradation.…”
Section: Polysaccharide Depolymerasesmentioning
confidence: 99%
“…Slices were preincubated for 30 min on ice in dissection buffer supplemented with 10 mM HEPES, 1× penicillin/streptomycin (Biochrom) and 50 μg/ml gentamycin (Sigma-Aldrich). Where indicated, slices were incubated with 4 μg/ml endosialidase (endo) (Stummeyer et al, 2005), which reliably and with high specificity removes polySia from the surface of living cells in culture and in tissues (Jakobsson et al, 2012). After transfer to Millicell cell culture inserts (PICM0RG50, Merck-Millipore) in six-well plates, slices were cultured for 1 day at 37°C and 5% CO 2 in growth medium 1 comprising Neurobasal medium (Life Technologies) containing 1× B27 supplement (Life Technologies), 32 mM D-glucose, 2 mM L-glutamine, 1× penicillin/streptomycin and 4 μg/ml endo, where indicated.…”
Section: Western Blottingmentioning
confidence: 99%
“…Folding of the trimeric endoNF involves auto-proteolytic release of its C-terminal chaperone domain in a Ser-Lys dyad reaction (Mühlenhoff et al, 2003;Schwarzer et al, 2007;Schulz et al, 2010a;Schulz and Ficner, 2011). The release of the chaperone domain increases thermal stability of endoNF (Schwarzer et al, 2007) and unmasks a polySia binding site located in the stalk domain conferring processivity to the enzyme (Schwarzer et al, 2009;Jakobsson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…About thirty genomes of E. coli K1-specific phages have been characterized so far and all contain a gene that encodes an endoN (Jakobsson et al, 2012). The tailspike of coliphage K1F (endoNF) serves as a paradigm for all these enzymes as its function, folding properties, and crystal structure in the apo-and substrate-bound form have been well characterized (Mühlenhoff et al, 2003;Stummeyer et al, 2005;Schwarzer et al, 2007Schwarzer et al, , 2009Schulz et al, 2010bSchulz et al, , 2010c.…”
Section: Introductionmentioning
confidence: 99%